Peningkatan Bodily Kinesthetic dan Intra Personal Skill melalui Pendekatan Saintifik pada Pembelajaran IPA - Ngurah Ayu Nyoman Murniati; Arri Handayani; Mahmudah Mahmudah (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2017)
Understanding the potential of self is very necessary to be given in an effort to prepare a tough generation of 21 century who have adequate skills. The fundamental problem is the low ability of self-recognition of kinesthetic response and communication between person and person in his group. Marginal children as well as groups of children The changes and demands of school curricula are directed to the development of the 21st-century generation. The study of kinesthetic and interpersonal skill indicators as part of the development of basic skills is developed in both formal and non-formal education. This study aims to analyze the increase of bodily-kinesthetic and interpersonal skill in science learning in MTs through the application of the scientific approach. The design of this research is quasi-experiment (Quasi-Experimental Design) which form Posttest-Only Control Design. The population in this research is all students of class VIII MTs Negeri Mranggen. The sample consists of two classes taken with simple random sampling technique. There is a significant difference between bodily-kinesthetic and interpersonal skills that use learners' worksheets with the teaching materials used in the school. The difference is indicated by the average bodily-kinesthetic and interpersonal skill values between experiment classes that have a higher value than the control class. Data were analyzed by using the right side t-test. Based on the results of data analysis can be concluded that the application of the scientific approach has an effect on the increase of bodily-kinesthetic and interpersonal skill of MTs students.